Growth rate enhancement of tiger milk mushroom using electrical stimulation techniques - Mohd Jamil, Nor Azreen (2018)
Slow growth rate of some varieties of mushrooms, including tiger milk mushroom, demands the application of such growth enhancement techniques including through electrical stimulation techniques. However, the only electrical technique that has been reported is through pulse electrical technique at high voltage, which is not cost effective and has many limitations in upscaling to suit commercial applications. Therefore, the objective of this study is to enhance the growth rate of tiger milk mushroom (Lignosus rhinocerus) by applying different electrical stimulation techniques, specifically at low electrical field strengths or high strength with feasible techniques. Mycelium of tiger milk mushroom at early developmental stage was exposed to injection of direct current, electric field and corona discharge respectively for five days, at various combinations of electric field strength, time duration and frequency of application. Results show that none of the treated mycelium exhibited growth rate acceleration upon discontinuous exposure to direct current at 0.03 A to 0.9 A, electric field at 350 V/cm from a Van de Graff generator and corona discharges at 5 kV electrical strength. Continuous exposure (five hours) to 1.1-1.3 A direct current has retarded the mycelium growth at the anode region. In contrast, discontinuous exposure to electric field for short period by a DC power supply at 30 V/cm has accelerated the mycelium growth rate up to 8%. The positive impact was declined with the reduction of electric field strength to 8.2 V/cm. The growth rate of the mycelium was successfully increased up to 10% by corona discharges through multiple needles at 5 kV for five hours continuously. Application of this technique on the mycelium at intermediate development stage for four weeks has resulted in 16% enhancement on the mycelium growth rate and up to 56% to the yield of tuber. Myco-chemical analysis on the tuber of the corona- treated group did not show a significant variation in the total flavonoid content and metabolite chromatogram pattern as compared to the control groups and the reference groups. It can be concluded that continuous application of this feasibly technique of corona discharges through multiple needles at 5 kV by using a small scale Van de Graff generator was the best electrical stimulation technique for growth rate and yield enhancement of tiger milk mushroom. This finding will help in the development of a suitable design of the successful system to fit large scale mushroom cultivation without repeating the unsuccessful parameters.